Handbook of Atomization and Sprays Theory and Applications - Ashgriz, Nasser (Springer eBooks., 2011)
The Handbook of Atomization and Sprays presents the fundamentals, as well as applied material from all fields into one thorough, comprehensive resource. Subject areas included in the reference are droplets, theoretical models and numerical simulations, phase Doppler particle analysis, applications, devices and more. The handbook also covers: -Fundamental physics of the atomization process and the theoretical models and numerical simulations of spray -Experimental techniques for spray characterization and applications, as well as mechanisms of atomization -A wide range of industrial applications including but not limited to spray coating, medical, healthcare and agricultural sprays, spray cooling, and mass spectrometry, to name a few. Authored by the leading researchers and professionals in the spray and atomization field, The Handbook of Atomization and Sprays is a must-read for researchers and professional engineers working in the field.